Effects of maternal iodine nutritional status on neurodevelopmental and cognitive function of rat offspring - Fu, Min; Wu, Wen; Guo, Wenxing; Jin, Qi; Meng, Qi; Gao, Yuanpeng; Yang, Rui; Yang, Ying; Wang, Zihao; Zhang, Wanqi (Frontiers in Nutrition, 2022)
Objectives: This study aimed to explore the effect of maternal iodine status on the brain development of offspring in rats. Since human studies can’t remove the interference of environmental factors and other nutrients. Methods: 48 female Wistar rats were randomly divided into four groups: low iodine (LI), normal iodine (NI), 10-fold high iodine (10HI) and 50-fold high iodine (50HI). The rats were sacrificed on the 15th day of pregnancy and lactation after collecting 24-h urine. The iodine concentration in 24-h urine, blood and placenta of pregnant rats, 24-h urine, blood and mammary glands of lactating rats were determined by Inductively Coupled Plasma Mass Spectrometry. The thyroid hormone of pregnant and lactating rats was detected by Chemiluminescence. The offspring were subjected to the Morris water maze on the 10th day after birth. Serum was collected to detect the thyroid hormone of offspring. The protein expression of neuroendocrine-specific protein (NSP)-A and brain-derived neurotrophic factor (BDNF)in the offspring brain were studied. Results: Iodine storage in the placenta during pregnancy and mammary glands during lactation was positively correlated with iodine intake, and the placenta and mammary glands iodine storage in the 50HI group was significantly higher than that in the NI group (P=0.022 and P=0.003). Compared with the NI group, the offspring’s TSH level was significantly higher in the 10HI group (P=0.046), and the FT4 level was significantly lower in the 50HI group (P=0.032). The Morris water maze showed that LI and 50HI groups required longer time and distance to find the platform than the NI group (P<0.001). The platform crossing numbers in LI and 50HI groups decreased significantly (P<0.001). The expression of NSP-A in offspring brain was lower in the 10HI and 50HI groups when compared with the NI group (P=0.026 and P=0,008). BDNF expression levels was significantly lower in LI, 10HI and 50HI groups compared with the NI group (P<0.001). Conclusion: Maternal iodine intake affects iodine storage in the placenta and lactating mammary gland, which in turn affects thyroid function in offspring and the expression of BDNF and NSP-A, which associated with neurodevelopment and affected by thyroid hormones.